Electrochemical immunosensor to detect breast cancer marker CA 15-3 antibody. (December 2022) - Patil, S.M.; Karade, V.C.; Kim, J.H.; Chougale, A.D.; Patil, P.B.
Abstract: Significant progress has been made in developing electrochemical immunosensors for the detection of various cancer-specific antigens. Still, the electrochemical immunosensors to detect cancer-specific antibodies have not been developed to date. We report a novel sandwich-type electrochemical immunosensor to detect cancer-specific antibodies anti-CA 15-3. HRP conjugated antibodies specific to analyte antibodies were used to construct a sandwich-type assay for signal amplification. The amine-functionalized reduced graphene oxide used to modify the electrode provided -NH2 functional groups for antigen immobilization. The fabricated antibody sensor exhibited a wide linear range of 8 orders of magnitude with a detection limit of 0.0001 ng mL –1 . The immunosensor exhibited good specificity, reproducibility and stability which demonstrated reliable detection in human serum samples. This work is the first report of quantitative estimation of anti-CA 15-3 by electrochemical immunosensor. Here anti-CA 15-3 has been used as a model antibody and the assay can be redesigned to detect other antibodies. Graphical Abstract: ga1